Familial Progressive Hyperpigmentation: A Case Report - Monica Yadav; Sugandha Ghonasgi; Rohit Shah; S. M. Meghana (Case Reports in Dentistry)
Familial progressive hyperpigmentation (FPH) is a rare genodermatosis characterized by hyperpigmented patches in the skin and mucous membranes, present in early infancy, and increase in size and number with age. The genetic basis for FPH remains unknown. We report an unusual case of familial progressive hypermelanosis in a 17-year-old male patient with family history, who presented with a peculiar progressive oral pigmentation disorder. Diagnosis was confirmed by a series of hematological, biochemical, and histopathological investigations. Our paper stresses the need for the dentist to be aware of the systemic conditions that can also manifest in the oral cavity.